Association of an inter-arm systolic blood pressure difference with all-cause and cardiovascular mortality: An updated meta-analysis of cohort studies. (15th June 2015) - Cao, Kaiwu; Xu, Jingsong; Shangguan, Qing; Hu, Weitong; Li, Ping; Cheng, Xiaoshu; Su, Hai
Abstract: Objective: To evaluate whether an association exists between an inter-arm systolic blood pressure difference (sIAD) and all-cause and cardiovascular mortality. Methods: We searched for cohort studies that evaluated the association of a sIAD and all-cause or cardiovascular mortality in the electronic databases Medline/PubMed and Embase (August 2014). Random effects models were used to calculate pooled hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Nine cohort studies (4 prospective and 5 retrospective) enrolling 15, 617 participants were included. The pooled HR of all-cause mortality for a sIAD of ≥ 10 mm Hg was 1.53 (95% CI 1.14–2.06), and that for a sIAD of ≥ 15 mm Hg was 1.46 (1.13–1.88). Pooled HRs of cardiovascular mortality were 2.21 (95% CI 1.52–3.21) for a sIAD of ≥ 10 mm Hg, and 1.89 (1.32–2.69) for a sIAD of ≥ 15 mm Hg. In the patient-based cohorts including hospital- and diabetes-based cohorts, both sIADs of ≥ 10 and ≥ 15 mm Hg were associated with increased all-cause (pooled HR 1.95, 95% CI 1.01–3.78 and 1.59, 1.06–2.38, respectively) and cardiovascular mortality (pooled HR 2.98, 95% CI 1.88–4.72 and 2.10, 1.07–4.13, respectively). In the community-based cohorts, however, only a sIAD of ≥ 15 mm Hg was associated with increased cardiovascular mortality (pooled HR 1.94, 95 % CI 1.12–3.35). Conclusions: In the patient populations, a sIAD of ≥ 10 or of ≥ 15 mm Hg could be a useful indictor for increased all-cause and cardiovascular mortality, and a sIAD of ≥ 15 mm Hg might help to predict increased cardiovascular mortality in the community populations.